Apponyi Albert jubileumi születésnapjai a kultusz jegyében - Anka, László (Közép-Európai Közlemények, 2016)
Count Albert Apponyi (1846-1933) was active in politics for sixty-one years of his life. Over the course of decades, popular opinion of him continually shifted. His father had been the last chancellor of the feudal Hungarian Kingdom, which had been swept away as a result of the 1848 Revolution. His father’s ensuing unpopularity had thus hurt his embryonic career, but the Great Military Defense Debateof 1889 was what changed all of that, when Apponyi forced the government to back down. As a result Apponyi earned a nationwide reputation as a great orator. During the decades of the Dualistic Era, this popularity proved to be relative, however. The peace treaty negotiations that closed WWI were what brought about the final change on his behalf, for it was at that time when he gave his so-called „apologia” (in Paris on January 16th, 1920), which provided the foundations for the unfolding revisionist principle and stated that the peace treaty was fundamentally unfair. Afterwards Apponyi’s national admiration took off. His 75th, 80th and 85th birthday celebrations were important moments in the evolution of his adulation, all of which were celebrated publicly. Numerous speeches, pamphlets, poems, grantings of honorary citizenship and documents lauding Apponyi were made on the occasions of these jubilees. The men behind the Apponyi hero worship treated his life story in a biased manner though, distorting the role he had played after 1920 and devoting minimal attention to his pre-WWI career. Those who did invoke that period did so very selectively, misconstruing facts and wrongly crediting Apponyi for the actions of others. They devoted hardly any attention to Apponyi’s stints as Speaker of the House of Representatives and as Minister of Culture, noting them only in passing. Apponyi’s divisive political personality during the pre-WWI period and the search for scapegoats to pin the blame on for losing the war were the reasons why that part of his career was so thoroughly ignored.